Like a Chameleon: Deception Language in Spy x Family - Annas Secario Choirul Huda; Ryo Adi Buwono; Muhammad Fikri Rafi; Daffa Mahfud Suseno; Wisnu Arya Nandwita (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Critical analysis of deceptions in fictions can provide a comprehensive discourse. The study examined deception within the Forger family in Spy x Family, where each member hides their true identity: Loid is a spy, Yor an assassin, and Anya an esper. Using Shuy's (2012) theory, a qualitative analysis of their dialogue identified nine types of deception: giving overly detailed or marginally relevant details, complicating stories, providing unusual or external associations, displaying subjectivity, correcting spontaneously, acknowledging memory loss, and excessive self-reference. The most common deception type in family interactions is giving marginally relevant details. The research highlights deception's key role in the anime's plot and character relationships and serves as a foundation for future studies on deception.